Evaluation the Effect of Phytosterol Fraction of Chenopodium Murale in Comparison with Tacrolimus on Mice Induced Atopic Dermatitis - Zahra Hassan; Tuka hassan; Ahmed Abu- Raghif (College of Pharmacy University of Baghdad, 2023)
Atopic dermatitis (atopic eczema), is a common familial chronic inflammatory skin disease, determined by xerosis, itching, scaly and erythematous skin lesions, and high serum levels of IgE. Between 10 to 20% of children and 1 to 3% of adults worldwide affected by it and has negative medical and social effect on patients and their families. To evaluate the effectiveness of Phytosterol Fraction of Chenopodium Murale on induced atopic dermatitis (AD) of mice; Forty mice were included in the study, divided in to four groups (10 mice/group): apparently healthy, induced AD without treatment, induced AD treated with Tacrolimus 0.1% ointment, and induced AD treated with Phytosterol Fraction of Chenopodium Murale cream 3% topically. Examination of histopathology was done and skin homogenates levels also measured using Mann Whitney U test to determine meanSD. Levels of WBC, Eosinophil, skin tissue homogenate of IL-13 and IL-4, serum IgE, and histopathological scores were significantly increased among induced non treated AD group in comparison with control group. Comparisons of non-treated induced AD group with Chenopodium Murale or Tacrolimus treated groups; shows a significant reduction in the levels of all studied parameters' (WBC, Eosinophil, skin tissue homogenate of IL4- and IL-13, serum IgE, observational severity score, and histopathological scores) after the application of Tacrolimus 0.1% ointment or Chenopodium Murale cream 3% topically. The comparison between the effect of topical application of tacrolimus and Phytosterol Fraction on the studied variables shows that the level of WBC and thickness of epidermis and inflammatory cells were significantly lower after tacrolimus treatment, while high significant reduction was founded in parakeratosis and score of observational severity among Chenopodium murale treated group in comparison with Tacrolimus treated group. In conclusion, the use of these therapeutic agents that target IgE, IL-4 and IL-13 could be promising in the treatment of AD.